PENELUSURAN RAGAM JENIS BAMBU DI KOTA LANGSA, ACEH - Ritonga, Muhammad Azli; Nurchalidah, Siti; Karmiati, Karmiati; Navia, Zidni Ilman; Suwardi, Adi Bejo (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Langsa City has a wealth of plant species that need to be studied, especially bamboo plants. This study aims to explore the types of bamboo found in Langsa City. The study was conducted from April to July 2019 using the exploration method. The method of sample collection by purposive sampling. The results showed that in Langsa City there were found 4 genera bamboo namely Bambusa, Gigantochloa, Schizostachyum, and Thyrsostachys which consisted of 6 species of bamboo namely Bambusa multiplex (Lour.) Raeusch. Ex Schhult., Bambusa vulgaris Schrad. Ex Wendl., Gigantochloa apus (J.A. & J.H.Schult.) Kurz, Gigantochloa atter (Hassk.) Kurz, Schizostachyum brachycladum (Kurz) Kurz, and Thyrsostachys siamensis Gamble. The most widespread bamboo distribution in Langsa was found in Langsa Lama and Langsa Baro amounted to 5 species.